Investigation of the Rs7041 Variable of Vitamin D-Connector Protein Gene Relation With Pancreatic Involvement in Patients With Coronavirus Disease 2019 - Ozturk, Vuslat; Gul, Mehmet Ali; Aci, Recai; Keskin, Adem; Tozcu, Duygu; Cihangiroglu, Mustafa; Tekcan, Akin (Associação Médica Brasileira, 2025)
OBJECTIVE: This study aims to examine whether the presence of mutation exists in the vitamin D-connector protein gene rs7041 variant of the pancreatitis table for patients diagnosed with coronavirus disease 2019. METHODS: A total of 113 patients with normal pancreatic enzyme levels diagnosed with coronavirus disease 2019 and 120 patients with both coronavirus disease 2019 diagnosis and high pancreatic enzyme levels were included in the study. The rs7041 genotyping of the 11th single nucleotide variation in the vitamin D-connector protein gene was determined by polymerase chain reaction and restriction fragment length polymorphism methods. RESULTS: In the patient group with coronavirus disease 2019 diagnosis and high pancreatic enzyme levels, the vitamin D-connector protein gene rs7041 variance GG genotype ratio was determined to be higher than the normal coronavirus disease 2019 patients. As a result of comparisons between the two groups, the difference between the genotype ratios in the relationship was determined to be statistically significant (p=0.004). CONCLUSION: Coronavirus disease 2019 patients were determined that the rs7041 halves in the vitamin D-connector protein gene could be prone to pancreatitis formation. Different populations and work with more patient groups are needed to verify the results of the study.
Tekcan, Akin/0000-0001-7961-6657; Çapraz, Mustafa/0000-0001-9586-6509; Gül, Mehmet Ali/0000-0002-5849-0116; Kaya, Muhammed Taha/0000-0003-2744-4763; Tozcu Yilmaz, Duygu/0000-0002-3972-5442; Yigit, Serbulent/0000-0002-1019-3964; Öztürk, Vuslat/0000-0002-2620-6977; Aci̇, Recai̇/0000-0002-1517-3356; Cihangiroğlu, Mustafa/0000-0001-6148-5142; Keskin, Adem/0000-0003-1921-2583;
Keywords: COVID-19; Pancreas; Vitamin D; Vitamin D Binding Protein; SNP